Impact of the COVID-19 pandemic on training sessions of young Japanese handball players: a questionnaire-based retrospective cohort study - Asai, K.; Nakase, J.; Yoshimizu, R.; Kimura, M.; Kanayama, T.; Yanatori, Y.; Kitaoka, K.; Hiroyuki, T. (Asian Journal of Sports Medicine, 2023)
Background:The training environment for handball, particularly for young athletes, was affected by the COVID-19 pandemic in 2019 and 2020.